1998
DOI: 10.1023/a:1011946314416
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The hydrolase activities for propranolol prodrugs and p-nitrophenylacetate in intestinal mucosa showed great species differences and those in human intestine were closer to those of rat intestine than dog intestine or Caco-2 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In addition, it was previously reported that intestinal hydrolysis shows no enantioselectivity toward propranolol derivatives in humans, rats, rabbits, and dogs, , with only monkey intestine showing enantioselective hydrolysis. CES2 isozymes are predominantly expressed in the intestine in most experimental animals, although dog intestine possesses no CES isozymes, but it seems that only monkey CES2 shows enantioselective hydrolysis of propranolol derivatives.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, it was previously reported that intestinal hydrolysis shows no enantioselectivity toward propranolol derivatives in humans, rats, rabbits, and dogs, , with only monkey intestine showing enantioselective hydrolysis. CES2 isozymes are predominantly expressed in the intestine in most experimental animals, although dog intestine possesses no CES isozymes, but it seems that only monkey CES2 shows enantioselective hydrolysis of propranolol derivatives.…”
Section: Discussionmentioning
confidence: 98%